A antecipação do ingresso da criança aos seis anos na escola obrigatória: um estudo no sistema municipal de ensino de Santa Maria/RS - Santos, Luciana Dalla Nora dos (2008)
This research is inserted in Curriculum, Teaching and School Practices line at Postgraduate Program in Education from UFSM. It had as purpose to know the ideas from teachers about admission of children, aged six, to obligatory school and its implications in the organization of beginning reading and writing teaching process. Studies from Ferreiro and Teberosky (1999), Ferreiro (1993, 2001, 2002), Bolzan (2001, 2002, 2007), Vygotski (1994, 1995), among others, were utilized as theoretical basis to develop this investigation. This research was carried out in Municipal System of Teaching from Santa Maria/RS, between April and December, 2007. The participants were twelve teachers, who developed their profession at first grade groups of Elementary School. The investigation was done through a qualitative narrative study, which focused on the teachers speeches/voices/narratives. The data search was carried out through some semi-structured interviews. The teachers, expressing their understanding about the children admission to school, allowed the construction of three categories: conceptions of childhood and children, conceptions of reading and writing and conceptions of pedagogical organization. In the elaboration of these categories, two movements arose: a retrospective movement and a prospective movement. In the retrospective movement, the teaching enlargement is thought in a retrospective view, from what the students do not know, and, thus, the teaching processes are organized, not considering the childhood as a period of development, what makes occur, in this way, the educational formalization. In the prospective movement, it was noticed that the organization of this first grade addresses to think of producing the childhood and of formalizing the education processes in a prospective way. We realized, thus, an educational construction movement directed to the students possibilities. In this way, it was pointed out that there are two realities being produced inside schools; on the one hand, the practice has been the motivator for of a wide children development and, on the other hand, the practice addresses to the existence of activities which ignore the children sociocultural nature. At last, the research allowed to perceive that to think, prospective or retrospectively, makes part of the own school production movement, which needs to be, constantly, reviewed and questioned in the institution as a whole.